2013
DOI: 10.1007/s00125-013-3000-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aliskiren on urinary cytokine/chemokine responses to clamped hyperglycaemia in type 1 diabetes

Abstract: Aims/hypothesis Acute clamped hyperglycaemia activates the renin-angiotensin-aldosterone system (RAAS) and increases the urinary excretion of inflammatory cytokines/chemokines in patients with uncomplicated type 1 diabetes mellitus. Our objective was to determine whether blockade of the RAAS would blunt the effect of acute hyperglycaemia on urinary cytokine/chemokine excretion, thereby giving insights into potentially protective effects of these agents prior to the onset of clinical nephropathy. Methods Blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Miller et al demonstrated that hyperfiltration responses to clamped hyperglycemia are related to intrarenal RAAS activation [15], [31]. Moreover, Cherney et al recently showed that RAAS blockade by aliskiren (a direct renin inhibitor) blunts the increased GFR as measured by inulin clearance provoked by hyperglycemia [32]. These findings are also consistent with our data, where we did not observe a significant association between glucose and eGFR CYSTATIN C in subjects with RAAS inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…Miller et al demonstrated that hyperfiltration responses to clamped hyperglycemia are related to intrarenal RAAS activation [15], [31]. Moreover, Cherney et al recently showed that RAAS blockade by aliskiren (a direct renin inhibitor) blunts the increased GFR as measured by inulin clearance provoked by hyperglycemia [32]. These findings are also consistent with our data, where we did not observe a significant association between glucose and eGFR CYSTATIN C in subjects with RAAS inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…Activation of the intrinsic RAAS is physiologically important in humans for regulating arterial blood pressure and for maintaining sodium and electrolyte hemostasis. In the setting of chronic hyperglycemia, overactivation of the RAAS is strongly implicated in the initiation and progression of DKD (10,(20)(21)(22)(23)(24). Organ-specific measurement of RAAS activation, however, has not been previously characterized in cohorts with long-standing T1D within defined subgroups of those with and without DKD (10).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 27 patients with type 1 diabetes mellitus and no nephropathy, treatment with aliskerin for 30 days reduced urinary excretion of IFN-a2 and IL-2. 77 Similarly, in 30 patients with hypertension and CKD, aliskerin treatment for 8 weeks reduced serum C reactive protein (CRP) levels. 78 Nevertheless, the addition of direct renin inhibitors to ARB therapy has not yielded consistent improvements in clinical outcomes, 79 diminishing enthusiasm for this strategy unless alternative, more efficacious modulators of noncanonic PRR signaling can be developed.…”
Section: Immunologic Effects Of Ras Manipulation In Humansmentioning
confidence: 99%